Implementing Project-Based Steam Instructional Approach in Early Childhood Education in 5.0 Industrial Revolution Era - Cahyorini Wulandani; Meida Afina Putri; Rahmalia Indah Pratiwi; Komareeyah Sulong (Indonesian Journal of Early Childhood Educational Research (IJECER), 2022)
The 5.0 industrial revolution era requires people to have competency such as critical thinking, problem solving, innovation, collaboration, and communication. The purpose of this study was to determine the application of a project-based STEAM learning approach to develop the skills of early childhood in this 5.0 era. This study used descriptive qualitative method. Data were collected using observation, interview, and documentation. Triangulation was used for data trustworthiness and data analysis referred to Miles and HubermanÔÇÖs. Results showed that STEAM project-based learning can be used to develop various skills of early childhood by connecting elements of science, technology, engineering, art and mathematics and applying some strategies including reflection, discovery, application, and communication in learning.